Hints to Mayor Election: Genre Analysis of the Political Advertisement On Aminullah – Zainal Posters in Aceh - Bustami Usman; Izzatul Rizki; Iskandar Abdul Samad (English Education Journal, 2019)
Political advertisement – sub-genre of promotional advertisement, takes an important role in the election, particularly Mayor Election.  Hence, this study made an effort on analyzing the element of this genre. The four posters from Aminullah – Zainal were the samples analyzed in this study. Likewise, the data were elaborated descriptively through genre analysis. Furthermore, Barron’s framework (2012) was employed as an instrument to collect the data about rhetorical patterns (RP).  The result of this study revealed that all of the political posters followed the rhetorical pattern of Barron framework. In addition, the seven moves suggested by Barron are the obligatory features of Aminullah – Zainal posters.